Belief Strength and Pedagogical Strategies in Integrating Islamic Values in ELT: A Comparative Study of Secular and Islamic Institutions in Indonesia - Nadira Syifa Azzahro; Faizal Risdianto (CV. Rustam, 2025)
This study explores how educators in Islamic and secular institutions in Indonesia differ in their beliefs and strategies for integrating Islamic values into English Language Teaching (ELT). Educators in Islamic schools, pesantren, and Islamic universities show very strong confidence, viewing integration as both a religious duty and a pedagogical requirement. In contrast, teachers in secular schools and universities maintain moderately strong but cautious beliefs due to the demands of neutrality and inclusivity in multireligious classrooms. Implementation practices also diverge sharply. Islamic institutions apply explicit strategies—such as Qur’anic readings, hadith-based vocabulary lessons, ILRP materials, and prayer routines—leading to short-term increases in religious motivation and long-term reinforcement of Islamic identity. Secular institutions use more implicit or universal-value approaches, including honesty-based writing tasks, ethical discussions, and tolerance-related themes, which foster social–moral development and multicultural identity formation. These differences reflect deeper institutional orientations and offer important implications for inclusive ELT curriculum and teacher training.